Mise en forme et objet du savoir géographique dans une compilation du XVIe siècle : les Navigationi et viaggi de Giovanni Battista Ramusio - Fiona Lejosne (L'Atelier du CRH)
The publication of the three-volume compilation Navigationi et viaggi in Venice between 1550 and 1559 is considered as a founding event in the history of modern geography. Ramusio, who gathered the texts, aimed at describing the whole of the œcumene through texts – among which travel writings, letters and official accounts. This paper questions the intentions and the tenets of such a project by an analysis of the form –the compilation– and of the representation of geographical knowledge through texts. Studying the choices in shaping the knowledge, and studying the aims of the Navigationi et viaggi collection reveals the conviction that there is a fundamental complementarity between the various types of knowledge, as well as between the various modalities of knowledge representation